KONFIGURASI POLITIK LEGISLASI JAMINAN PRODUK HALAL PERSPEKTIF FIQH SIYASAH - Widyawati Widyawati (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2022)
Act Number 33/2024 on Halal Product Guarantee was already issued by the Indonesian government in 2014. The main objective of this act is to ensure comfort, security, safety, and certainty of halal product availability for society in consuming and using products. However, the issues and debates around this bill have drawn severe attention from different parties, especially during deliberation as represented in political configuration. As it was known, political configuration constitutes legal drafting and its implementation as represented in the character and orientation of legal development. This paper concludes that political configuration in the legislation of halal product guarantee is democratic because it was conducted openly and gives room for public participation as well as legislative and executive bodies according to their function proportionally. This political configuration is in line with such principles found in fiqh siyasah as consultation (musyawarah), freedom (hurriyyah) and equality (musawah). This conclusion was drawn using primary and secondary data through the content analysis method. Primary data include official documents related to the bill and act of halal product guarantee, while secondary data refer to articles and books on halal product guarantee.